From UBE3A to Angelman syndrome: a substrate perspective - Sell, Gabrielle L.; Margolis, Seth S. (Frontiers in Neuroscience, 2015)
Angelman syndrome (AS) is a debilitating neurodevelopmental disorder that is characterized by motor dysfunction, intellectual disability, speech impairment, seizures and common features of autism spectrum disorders (ASDs). Some of these AS related phenotypes can be seen in other neurodevelopmental disorders (Williams, 2011;Tan et al., 2014). AS patients commonly carry mutations that render the maternally inherited UBE3A gene nonfunctional. Duplication of the chromosomal region containing the UBE3A gene is associated with ASDs. Although the causative role for UBE3A gene mutations in AS is well established, a long-standing challenge in AS research has been to identify neural substrates of UBE3A, an E3 ubiquitin ligase. A prevailing hypothesis is that changes in UBE3A protein levels would alter the levels of a collection of protein substrates, giving rise to the unique phenotypic aspects of AS and possibly UBE3A associated ASDs. Interestingly, proteins altered in AS are linked to additional ASDs that are not previously associated with changes in UBE3A, indicating a possible molecular overlap underlying the broad-spectrum phenotypes of these neurogenetic disorders. This idea raises the possibility that there may exist a “one-size-fits-all” approach to the treatment of neurogenetic disorders with phenotypes overlapping AS. Furthermore, while a comprehensive list of UBE3A substrates and downstream affected pathways should be developed, this is only part of the story. The timing of when UBE3A protein functions, through either changes in UBE3A or possibly substrate expression patterns, appears to be critical for AS phenotype development. These data call for further investigation of UBE3A substrates and their timing of action relevant to AS phenotypes.